PERSEPSI MASYARAKAT TENTANG PENGEMBANGAN PARIWISATA PULAU LEMBEH (STUDI DI KECAMATAN LEMBEH SELATAN KOTA BITUNG) - Ginting, Yolanda Dede Harbig; Tulusan, Femmy; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: In the development of tourism is seen and felt by the local society through thesense of eyesight, but, not all of them says that the tourism development are good or bad,because every individual has a different perception or view. The purpose of this researchto find out how the public perception of the development of Lembeh island tourism (studyof Lembeh Subdistricts of South, City of Bitung). This research uses descriptivequalitative approach method with describing data obtained from research resultsregarding the public perception about the development of Lembeh island tourism (studyof Lembeh Subdistricts of South, City of Bitung). In qualitative research, data collectionis done by in observation, depth interview and documentation.Tourism development is an effort to improvement of the society welfare byutilizing the tourism potentials are at once, which is an effort to preserve the culture ofsociety through the improvement and enhancement of tourism products and services.Other than that, the development of tourism should also be addressed to protection andpreservation of culture that are very dependent on the society and the tourist.Result of this research on public perception about the development of Lembehisland tourism (study of Lembeh Subdistricts of South, City of Bitung) not well seen fromsome perception factors that is: absorption, understanding or comprehension, assessmentor evaluation about tourism development of Lembeh island in District of South Lembeh isnot good. The overall conclusion of public perception about the development of Lembehisland tourism (study of Lembeh Subdistricts of South, City of Bitung) for current is notgood and has not been managed by the Government with the maximum. Then can insuggest is to the Government to be more managed with maximum and immediately do therepair, improvement in tourist spots and also for the visitors and local community inorder to keep the environment clean.Keywords: Perception, Tourism Development